ISLAMIC VALUE-DRIVEN COOPERATION IN SKILLS ACQUISITION AND MOBILITY FOR EMPOWERING MARGINAL SOCIETY - Abu Saim Mohammad Shahabuddin; Muhammad Hedayatul Islam (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2015)
Islam exhorts for cooperation in righteous and God conscious acts. This exhortation has individual and institutional implications for efforts geared towards promoting the welfare of less privileged marginal segment of society. Conceiving an institutional form of cooperation, this paper proposes and explains a program which will target at empowering this segment. The program is for developing non-professional skills which have to be founded on and inspired by the Islamic principles of cooperation and self-reliance. As non-professional skills are mostly learned informally and on-the-job, business houses will be the cooperator who will provide platforms for training. Members of a marginal segment of society will be the beneficiaries who will receive training for acquiring job skills and mobility towards achieving their self-reliance. Government organ will be a facilitating party that shall provide support for the collaborative venture to occur and sustain. Apart from Islamic principles of cooperation and self-reliance, this paper will draw upon the theory of social learning, theory of conforming to group norms and doctrine of market supervision (al-Hisbah) in Islamic civilization to expound the role of the triad—the cooperator, the beneficiaries, and the facilitator—in achieving the major outcomes of the program. =========================================== Islam mendorong kerjasama dalam kebaikan dan bertindak semata-mata karena Allah. Dorongan ini memiliki implikasi individual dan institusional dalam upaya mensejahterakan masyarakat marjinal yang kurang beruntung. Dalam suatu bentuk upaya kerjasama secara institusional, artikel ini menawarkan dan menjelaskan suatu program yang akan menargetkan dalam memberdayakan segmen ini. Program ini bertujuan untuk mengembangkan keterampilan non-professional yang dibentuk dan didorong oleh prinsip-prinsip Islam dalam kerjasama dan kemandirian. Keterampilan non-professional sebagian besar dipelajari secara informal dan disaat bekerja, tempat-tempat bisnis akan menjadi pembuat kerjasama yang akan menyediakan platform untuk pelatihan. Para anggota masyarakat di segmen marjinal ini akan menjadi penerima manfaat yang akan mendapatkan pelatihan untuk mendapatkan keahlian kerja dan mobilitas untuk mencapai kemandirian. Institusi pemerintah yang berkaitan akan menjadi fasilitator yang akan menyediakan dukungan bagi skema kolaboratif agar dapat diwujudkan dan berkelanjutan. Selain dari prinsip- prinsip kerjasama dan kemandirian dalam Islam, paper ini akan mengutip teori pembelajaran sosial, teori sesuai dengan norma-norma kelompok dan doktrin pengawasan pasar (Al-Hisbah) dalam peradaban Islam guna menjelaskan peranan tiga pihak yaitu pembuat kerjasama, penerima manfaat, dan fasilitator dalam upaya mencapai hasil-hasil utama dalam program tersebut.